Application of Autonomous Solar Energy-Powered Fishing Small Boat to Support Fisheries Food Security in Underserved Villages ff Demak Regency - Adenanthera Lesmana Dewa; Erika Saraswati; Malikus Sumadyo; Purwanto Purwanto; Muhammad Ikhsan Setiawan; Che Zalina Zulkifli; Mohd Fauzi Sedon; Fazilat Kodirova (Malikussaleh University, Aceh, Indonesia, 2026)
Fisheries-based food security in underserved coastal villages remains vulnerable due to limitations in fishing capacity, rising fuel costs, environmental degradation, and restricted access to modern fishing technologies. These challenges significantly affect the productivity and income of small-scale fishers, ultimately influencing the availability and affordability of fish as a primary source of protein for coastal communities. In many coastal areas of Indonesia, particularly in underserved villages, conventional fishing activities continue to rely heavily on fossil-fuel-powered boats, resulting in high operational expenses and increased greenhouse gas emissions. Consequently, there is a growing need for innovative and sustainable technological solutions that can improve fisheries productivity while supporting environmental conservation and community welfare. This study presents the design, development, and application of an autonomous, solar-powered small fishing boat aimed at enhancing sustainable fisheries production in underserved villages in Demak Regency, Indonesia. The proposed system integrates renewable energy harvesting through photovoltaic panels, autonomous navigation technology, fish location sensing, and intelligent route optimization to reduce dependence on fossil fuels while increasing operational efficiency and fishing effectiveness. A mixed-method approach was employed, combining engineering design, prototype development, laboratory validation, field deployment, and pilot testing involving local fishers. Stakeholder feedback was also collected to evaluate usability, acceptance, and potential socioeconomic impacts. The results indicate that the solar-powered autonomous fishing boat reduces operational fuel costs by approximately 95%, increases fishing efficiency by 42%, and decreases greenhouse gas emissions by an estimated 1.8 tonnes of CO? per vessel annually. Furthermore, the system demonstrates reliable navigation performance and contributes to safer fishing operations by reducing human workload and optimizing fishing routes. The adoption of this technology has the potential to increase fisher income, strengthen local food security, and support sustainable fisheries management. This innovation aligns with national strategies for renewable energy utilization, blue economy development, and rural economic empowerment, offering a scalable and environmentally friendly solution for coastal regions facing similar socioeconomic and ecological challenges.